South aisle - Ghosh, Ayan (2023)
St. Thomas Church was built long before electricity was available, and thus, it relied on natural light for illumination. The north and the south walls are divided by rows of tall windows, which allow sunlight and air circulation when the church is used for service on Sundays. Over the years, some of the windows got covered in stained glass.